Application of Positive Aspect Ability to Increase Self-Actualization for Low Self-Esteem Patient - Rosmiati; Ajeng Silvia Nurislami; Salwa Amalia; Suhanda (Inspirasi Foundation, 2022)
Objective: To present care with the intervention of applying positive aspects of ability to increase self-actualization for patients with low self-esteem. Method: This case study design with a nursing care approach which includes assessment, determining diagnoses, nursing plans, nursing actions and nursing evaluations. In this case study the method used is descriptive analytic. The subject of this case study is 1 client with low self-esteem in the Tanjung BLUD Room, Banjar City General Hospital. With data collection techniques include interviews, observation and documentation studies. Results: The results of nursing care, it was found that subjective data was rejected by a woman, often locked herself at home because she felt ashamed and was often ridiculed by her friends, patients did not participate in activities in the community. And the objective data are low and weak voices, speech is not audible, the patient looks restless, confused and looks sad, the patient sometimes seems to be talking to himself, his eyesight is lacking, eye contact is lacking, the patient looks a little lowered and his concentration is easily distracted. There are nursing problems found, namely low self-esteem. So that the intervention given is the application of positive aspects of ability. Conclusion: The intervention of applying positive aspects of ability is proven to be effective in increasing self-actualization of patients with low self-esteem. As long as the recommended action is the patient is cooperative.